Targeting Prostate Cancer Stem Cells with Alpha-Particle Therapy - Ceder, Jens; Elgqvist, Jörgen (Frontiers in Oncology, 2017)
Modern molecular and radiopharmaceutical development has brought the promise of tumor-selective delivery of antibody-drug conjugates to tumor cells for the diagnosis and treatment of primary and disseminated tumor disease. The classical mode of discourse regarding targeted therapy has been that the antigen targeted must be highly and homogenously expressed in the tumor cell population, and at the same time exhibit low expression in healthy tissue. However, there is increasing evidence that the reason cancer patients are not cured by current protocols is that there exists subpopulations of cancer cells that are resistant to conventional therapy including radioresistance, and that these cells express other target antigens than the bulk of the tumor cells. These types of cells are often referred to as cancer stem cells (CSCs). The CSCs are tumorigenic and have the ability to give rise to all type of cells found in a cancerous disease through the processes of self-renewal and differentiation. If the CSCs are not eradicated, the cancer is likely to recur after therapy. Due to some of the characteristics of alpha-particles, such as short path length and high density of energy depositions per distance travelled in tissue, they are especially well suited for use in targeted therapies against microscopic cancerous disease. The characteristics of alpha-particles further make it possible to minimize the irradiation of non-targeted surrounding healthy tissue, but most importantly; make it possible to deliver high absorbed doses locally and therefore eradicating small tumor cell clusters on the sub millimeter level, or even single tumor cells. When alpha-particles passes through a cell they cause severe damage to the cell membrane, cytoplasm, and nucleus, including double-strand breaks of DNA that are very difficult to repair for the cell. This means that very few hits to a cell by alpha-particles are needed in order to cause cell death, enabling killing of cells, such as CSCs, exhibiting cellular resistance mechanisms to conventional therapy. This paper presents and evaluates the possibility of using alpha-particle emitting radionuclides in the treatment of prostate cancer, and discusses the parameters that have to be considered as well as pros and cons of...